Determinan Investasi Asing Langsung di Negara Berkembang-8 - Putri, Fitri Anisa Nusa; Muhdir, Ibnu; Hanafi, Syafiq Mahmadah (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
The flow of foreign capital (FDI) into a country can be beneficial to the host country and for multinational companies as a form of external financing for the host country. This study aims to analyze and explain the factors that influence the foreign direct investment inflow of Developing-8 countries from 2012 to 2021 using a panel data regression model through fixed-effect approaches. This study found that the size of markets and trade openness have a significant positive impact on FDI in developing eight countries. Meanwhile, the availability of natural resources has significantly negative effects, but inflation and infrastructure have no significant impact on the flow of FDI into developing eight countries. To boost the inflow of FDI, it is also important for governments to be able to make appropriate and profitable policies for countries and companies that are beneficial to countries and domestic firms.